COVID-19 Pandemic and its Effects on Mental Health: Challenges of Senior Citizens in Nepal - Acharya, Milan; Adhikari, Minraj (Interdisciplinary Research in Education, 2023)
This study explores the mental health problems of senior citizens (above 60 years) due to the COVID-19 pandemic in Kirtipur municipality. A qualitative research design with purposive sampling was used to choose the senior citizens and the study area. Data were taken from ten in-depth interviews and ten observations. Data were analyzed through thematic and verbatim methods. It is found that senior citizens had mental tension such as losing self-confidence, anxiety, forgetfulness, and loss of interest in work due to the COVID-19 pandemic. Based on this study, it is recommended that the Kirtipur municipality must identify the causes of the mental problems of senior citizens and support them to minimize the effects.